AB0609 Costunolide inhibits rankl-induced osteoclast differentiation by suppressing rankl-mediated c-fos transcriptional activity. (23rd January 2014) - Lee, C.-H.; Yoo, W.-H.; Jeong, Y.-G.; Oh, J.-M.; Lee, M.-S.; Lee, S.-I.; Cheon, Y.-H.; Kwak, H.-B.
Abstract : Background: Costunolide, a sesquiterpene lactone, exhibits anti-inflammatory and anti-oxidant propertiesand mediates apoptosis. However, its effects and mechanism of action in osteoclasts remains unknown. Objectives: We investigated the role of constunolide in RANKL-induced osteoclast differentiation. Methods: Osteoclast formation was evaluated in bone marrow cells (BMC) in the presence or absence of constunolide. The expression of c-fos and NFATc1 mRNA in osteoclast precursor were assessed by RT-PCR. The levels of c-fos and NFATc1 protein were assessed by western blot. Also the MAPKs and NF-κB pathways were measured using Western blot analysis. Results: we found that costunolide significantly inhibited RANKL-induced BMM differentiation into osteoclasts in a dose-dependent manner without affeting cytotoxicity. Costunolide did not regulate the early signaling pathways of RANKL, including the mitogen activated protein kinase (MAPK) and NF-κB pathways. However, costunolide suppressed nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1) expression via inhibition of c-Fos transcriptional activity without affecting RANKL-induced c-Fos expression. The inhibitory effects of costunolide were rescued by overexpression of constitutively active (CA)-NFATc1. Conclusions: Taken together, our results suggest that costunolide inhibited RANKL-induced osteoclast differentiation by suppressing RANKL-mediated c-Fos transcriptional activity. Disclosure of Interest: None Declared